Model-based predictive torque control of open-end winding IPMSMs driven by direct self-control - Lee, Hyung Woo; Park, Hyeon Jun; Lee, Kyo Beum (Journal of Power Electronics, 2024)
This paper proposes a method for the torque ripple reduction of an open-end winding interior permanent magnet synchronous motor (OEW-IPMSM) using direct self-control (DSC). The conventional DSC has been researched in high-power systems because of its advantages in terms of a low switching frequency and a fast response of torque. Nevertheless, high torque ripple is a disadvantage of the conventional DSC. This is because the trajectory of the stator flux is controlled in the shape of a hexagon for lower switching frequencies and by applying hysteresis torque control. In this paper, predictive torque control using a mathematical model of an OEW-IPMSM is presented to improve the quality of the torque control. In addition, the presented method addresses the trajectory control of the flux using the diverse voltage vectors of the dual inverter. The validity of the presented method is demonstrated by simulations and experimental results.
Keywords: Direct self control; Dual inverte with isolated power source; Dual inverters; Interior permanent magnet synchronous motor; Isolated power; Low switching frequency; Open-end winding IPMSM; Open-end windings; Power sources; Predictive torque controls; Direct self-control; Dual inverter with isolated power source; Open-end winding IPMSM; Predictive torque control